Algorithms for Sensor Systems 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers - Scheideler, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, held in Bordeaux, France, in July 2010. The 15 full papers and two brief announcements were carefully reviewed and selected from 31 submissions. The workshop aimed at bringing together research contributions related to diverse algorithmic and complexity-theoretic aspects of wireless sensor networks. In 2010 the focus was extended to comprise also contributions about related types of networks such as ad hoc wireless networks, mobile networks, radio networks and distributed systems of robots.
Improved Local Algorithms for Spanner Construction -- Planar Hop Spanners for Unit Disk Graphs -- Brief Announcement: Hierarchical Neighbor Graphs: A Sparse Connected Structure for Euclidean Point Sets -- Minimum Energy Broadcast on Rectangular Grid Wireless Networks -- Scheduling Multicast Transmissions under SINR Constraints -- Deterministic Recurrent Communication and Synchronization in Restricted Sensor Networks -- k ?+? Decision Trees -- Brief Announcement: Regional Consecutive Leader Election in Mobile Ad-Hoc Networks -- From Key Predistribution to Key Redistribution -- In-network Coding for Resilient Sensor Data Storage and Efficient Data Mule Collection -- Monitoring Churn in Wireless Networks -- Lifetime Maximization of Monitoring Sensor Networks -- MSDR-D Network Localization Algorithm -- Virtual Raw Anchor Coordinates: A New Localization Paradigm -- Self-localization Based on Ambient Signals.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer system performance; Computer software; Computer Science; Algorithm Analysis and Problem Complexity; System Performance and Evaluation; Computation by Abstract Devices; Software Engineering; Computer Communication Networks; Special Purpose and Application-Based Systems